Long QTc in hypertrophic cardiomyopathy: A consequence of structural myocardial damage or a distinct genetic disease? - Cava, Francesco; Micolonghi, Caterina; Musumeci, Maria Beatrice; Petrucci, Simona; Savio, Camilla; Fabiani, Marco; Tini, Giacomo; Germani, Aldo; Libi, Fabio; Rossi, Carla; Visco, Vincenzo; Pizzuti, Antonio; et al. (Frontiers in Cardiovascular Medicine, 2023)
Hypertrophic cardiomyopathy (HCM) is an autosomal dominant disease, characterized by asimmetric left ventricular hypertrophy. This condition is often associated with electrocardiographic abnormalities including QTc prolongation occurring in 13% of affected patients. The main explanation for the prolonged QTc in HCM is myocardial hypertrophy and the related structural changes. However, other mechanisms, including long QT syndrome (LQTS) genes mutations, may be involved. In our study we explored the hypothesis of a distinct genetic basis underlying QTc prolongation in HCM by investigating the potential co-inheritance of pathogenic gene variants associated with LQTS and HCM. For this purpose, starting from a cohort of 150 HCM patients carrying pathogenic variants in sarcomere genes, we selected 25 patients carrying a QTc prolongation unexplained by any other cause. The NGS analysis was performed with Illumina TrueSight Cardio panel genes on Illumina MiniSeq platform. We identified pathogenic/likely pathogenic variants in the KCNQ1 in two patients (c.1781G>A, p. Arg594Gln; c.532G>A, p. Ala178Thr) (8%). Variants of uncertain significance were identified in SCN5A, KCNJ5, AKAP9 and ANK2 in four patients (16%). Although the results are limited by the small number of patients included in the study, they highlight a minor contribution of LQTS genes for QTc prolongation in HCM patients. The screening for ion channel genes mutations may be considered in HCM patients with prolonged QTc unexplained by any other cause. This in-depth molecular diagnosis may contribute to improve risk stratification and treatment planning.